Social Media and the Constraint of Reality: Critiquing the FOMO Phenomenon during Coldplay Jakarta 2023 Concert - Bhaskara Chandra; Crysceline Zianet Tewal; Maha Putri Indah Chandra Kirana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This article examines the influence of social media on the Fear of Missing Out (FOMO) phenomenon and the constraint of reality in society, with a specific focus on the Coldplay Jakarta 2023 Concert. The research aims to critically analyze the FOMO phenomenon on social media that emerged during the Coldplay Jakarta 2023 Concert, providing insights into the reality disparities in society. This study adopts a qualitative research method through online-distributed open-ended questionnaires to the audience of the Coldplay Jakarta 2023 Concert. Variables investigated in this research encompass responses to the phenomenon and the social realities that emerged during the Coldplay Jakarta 2023 Concert through various dimensions and indicators. The research findings indicate that social media has a significant influence in creating the FOMO phenomenon at the Coldplay Jakarta 2023 Concert across various societal segments. Although the FOMO phenomenon induced by social media at the Coldplay Jakarta 2023 Concert can impact diverse segments of society, social media does not contribute to the formation of disparities in society.